Feasibility and safety of the direct current cardioversion at the time of left atrial appendage occlusion for patients with atrial fibrillation - Meng, Xian Sai; Chen, Tao; Wang, Xin Yan; Lu, Xu; Hu, Jia; Shen, Juan; Guo, Jun (Frontiers in Cardiovascular Medicine, 2023)
Background With an increasing number of patients undergoing left atrial appendage occlusion (LAAO), more attention is being paid to relieving clinical symptoms and improving the quality of life of these patients. For patients with atrial fibrillation (AF), direct current cardioversion (DCCV) is an alternate, nonpharmacological choice to restore sinus rhythm and relieve clinical symptoms. Objectives The purpose of this study was to assess the feasibility and safety of the DCCV at the time of LAAO for patients with AF. Methods Forty patients were enrolled in the DCCV group undergoing the DCCV at the time of LAAO. The control group undergoing LAAO alone was formed by 1:1 matching. Results In the DCCV group, cardioversion was immediately successful in 30 (75%) patients, of which 12 (40%) had AF recurrence at the three-month follow-up. The failed-DCCV group was older (73.70 ± 4.74 vs. 62.20 ± 9.01 years old, P = 0.000), had a faster postcardioversion heart rate (88.80 ± 16.58 vs. 70.97 ± 14.73 times, P = 0.03), and had a higher mean HAS-BLED score (4.00 vs. 3.00, P = 0.01) than the successful-DCCV group. No patients experienced periprocedural pericardial effusion, occluder displacement, device embolism, or >5 mm peridevice leakage. One patient experienced a transient ischemic attack (TIA) in the DCCV group during the follow-up. Conclusions The DCCV at the time of LAAO is feasible and safe for AF patients with contraindications for catheter ablation or AF recurrence after previous catheter ablation to restore the sinus rhythm and relieve clinical symptoms. The DCCV at the time of LAAO is more likely to succeed for younger patients and patients with lower HAS-BLED scores.